Enhanced Catalysis of Electrochemical Overall Water Splitting in Alkaline Media by Fe Doping in Ni3S2 Nanosheet Arrays - Zhang, Geng; Feng, Yu-Shuo; Lu, Wang-Ting; He, Dan; Wang, Cao-Yu; Li, Yong-Ke; Wang, Xun-Ying; Cao, Fei-Fei (ACS catalysis, 2018)
The development of bifunctional electrocatalysts with high performance for both hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) with earth-abundant elements is still a challenge in electrochemical water splitting technology. Herein, we fabricated a free-standing electrocatalyst in the form of vertically oriented Fe-doped Ni3S2 nanosheet array grown on three-dimensional (3D) Ni foam (Fe-Ni3S2/NF), which presented a high activity and durability for both HER and OER in alkaline media. On the basis of systematic experiments and calculation, the Fe-doping was evidenced to increase the electrochemical surface area, improve the water adsorption ability, and optimize the hydrogen adsorption energy of Ni3S2, which resulted in the enhancement of HER activity on Fe-Ni3S2/NF. Moreover, metal sites of Fe-Ni3S2/NF were proved to play a significant role in the HER process. During the catalysis of OER, the formation of Ni–Fe (oxy)hydroxide was observed on the near-surface section of Fe-Ni3S2/NF, and the introduction of the Fe element dramatically enhanced the OER activity of Ni3S2. The overall water splitting electrolyzer assembled by Fe-Ni3S2/NF exhibited a low cell voltage (1.54 V @ 10 mA cm–2) and a high durability in 1 M KOH. This work demonstrated a promising bifunctional electrocatalyst for water electrolysis in alkaline media with potential application in the future.